Trillium govanianum (Nagchattri): A promising rare and commercially important medicinal herb from higher altitudes of the Himalayas - Gupta, R; Sharma, N; Sood, H (Plant Science Today, 2026)
Secondary metabolites and bioactive compounds derived from naturally occurring sources have been the prime ingredients in modern health care as well as ancient medicine systems like Ayurveda, Yunani, and traditional folk medicines. A large number of plant species and their extracts are utilized to cure several human ailments. Trillium govanianum, belonging to the genus Trillium (family: Melanthiaceae alt. Trilliaceae), is a traditional medicinal herb of the Himalayan region used to cure joint pains, wounds, boils, dysentery, inflammation, menstrual and sexual disorders. T. govanianum root extracts have analgesic, anti-inflammatory, cancer-preventing, anti-fungal, and wound-healing activities. The main bioactive compounds present in this species are steroidal saponins. Indiscriminate and commercial harvesting in an unsustainable manner, along with various other biotic pressures, have created a synergistically severe menace toward the subsistence of T. govanianum in its natural habitat. Population assessment, conservative and in vitro proliferation methods pertaining to mass multiplication and advancement in ex–situ and in–situ environments are required for sustainable use of this species. In lieu of the significance of this herb, the present study aims at the exploration of phytochemical, ethnomedicinal, ecological, pharmacological, and conservational practices of T. govanianum for a better understanding of medicinal activities and sustainable use of this plant. This review summarised the potential resources of T. govaninanum in terms of biologically active compounds and their dependence on the local population. It focuses on the medicinal utility of T. govaninanum in different diseases and ailments.